KONSEP COURTROOM TELEVISION DALAM PERADILAN PIDANA SEBAGAI IMPLEMENTASI ASAS TERBUKA UNTUK UMUM - Putu Angga Pratama Sukma; Ni Komang Sutrisni (Jurnal Hukum Saraswati (JHS), 2025)
The concept of courtroom television has been implemented in Indonesia but not in its entirety. The implementation of courtroom television in criminal justice still has pros and cons which of course can provide education to the public about the law and carry out judicial supervision. This study uses a normative legal research method. The validity of courtroom television from the legal aspect of the principle of being open to the public, the openness of this trial is basically the State of Indonesia as a country of law requires the enforcement of nomocracy that can truly be implemented objectively. The concept of courtroom television or courtroom television is a complete and live broadcast covered by the press in the courtroom with a set of electronic media equipment by means of broadcasting, to divert and focus attention on all subjects (Judges, Clerks, Public Prosecutors, Lawyers, Defendants and Witnesses or Experts) without any review or comment. Open trials to the public, born from the principle of due process of law which is inseparable from the history of Human Rights.